Evaluation of sleep disturbances, gastrointestinal problems and eating behaviors in Turkish children with autistic disorder and PDD-NOS. Issue 2 (30th June 2020) - Gok, Sebahat; Ozturk, Serife Nur; Karaca, Rabia; İlbars, Serhat and Nogay, Nalan Hakime
Abstract : Purpose: The purpose of this study is to evaluate the relationship between sleep disturbances, gastrointestinal (GI) problems and eating behaviors in children who are diagnosed with autistic disorder (AD) and pervasive developmental disorder not otherwise specified (PDD-NOS). Design/methodology/approach: This study was conducted with 102 children who were diagnosed with autism spectrum disorder (ASD). Sleeping and GI (abdominal pain, constipation, diarrhea, vomiting, difficulty swallowing) problems in children were obtained by asking their parents using a questionnaire. The feeding assessment survey (FAS), brief autism mealtime behavior inventory (BAMBI) and food consumption frequency were used to obtain information about the children's eating habits. Findings: The BAMBI total score, food refusal and features of autism subscale scores of those with AD were higher than those in the PDD-NOS group ( p < 0.05). Sleeping, GI and eating problems are seen in those with AD more commonly than in those diagnosed with PDD-NOS. Originality/value: To the knowledge, this is the first study that compares GI, sleeping and eating problems in children with AD and PDD-NOS. Sleeping, GI and eating problems may be more frequent in children with AD than in those with PDD-NOS. The GI problem rate is higher in children with autism with sleeping problems than without sleeping problems.